2017
DOI: 10.1590/1678-69712017/administracao.v18n2p15-48
|View full text |Cite
|
Sign up to set email alerts
|

Digital Divide of Small and Medium-Sized Enterprises: An Analysis of Influencing Factors Using the Toe Theory

Abstract: Este artigo pode ser copiado, distribuído, exibido, transmitido ou adaptado desde que citados, de forma clara e explícita, o nome da revista, a edição, o ano e as páginas nas quais o artigo foi publicado originalmente, mas sem sugerir que a RAM endosse a reutilização do artigo. Esse termo de licenciamento deve ser explicitado para os casos de reutilização ou distribuição para terceiros. Não é permitido o uso para fins comerciais.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 25 publications
0
11
0
4
Order By: Relevance
“…Según Flores, Hernández y Garay (2020) la existencia de brechas digitales se encuentra asociada a accesibilidad y conectividad al internet, lo que genera desigualdad y está asociado con elementos sociales y económicos, esto es respaldado por Mendoza y Caldera (2014), Souza et al, (2017); Jiménez y Fernández (2016). Y de acuerdo con Venturini (2020), y Bielschowsky y Torres (2018), las brechas digitales igualmente se relacionan a diversos factores, tales como; tipo de dispositivos, apropiación de la tecnología y costo de los servicios.…”
Section: Discusión De Resultadosunclassified
“…Según Flores, Hernández y Garay (2020) la existencia de brechas digitales se encuentra asociada a accesibilidad y conectividad al internet, lo que genera desigualdad y está asociado con elementos sociales y económicos, esto es respaldado por Mendoza y Caldera (2014), Souza et al, (2017); Jiménez y Fernández (2016). Y de acuerdo con Venturini (2020), y Bielschowsky y Torres (2018), las brechas digitales igualmente se relacionan a diversos factores, tales como; tipo de dispositivos, apropiación de la tecnología y costo de los servicios.…”
Section: Discusión De Resultadosunclassified
“…The aim of the present study was therefore to analyse the validity of the Digital Divide Index proposed by Siqueira et al () in the context of PP, using the criteria listed by Jannuzzi (). This article integrates several other studies of the digital divide in which the authors use the data from the 2013 edition of the survey to (a) demonstrate how the index was created (Siqueira et al, ); (b) explore sectoral differences (Siqueira, Souza, & Reinhard, ); (c) validate the statistical technique employed in data analysis (Siqueira, Araujo, Souza, & Reinhard, ); and (d) find factors that contribute to bridging the divide (Souza et al, ).…”
Section: Public Policy and Indicatorsmentioning
confidence: 99%
“…Although ICT access seems to be widespread among SMEs (CGI, ) and is considered a less relevant factor in explaining the digital divide (Wielicki & Cavalcanti, ), even small differences in access to ICT result in differences in the intensity of ICT use. Hence, Souza, Siqueira, and Reinhard () have shown that ensuring access to ICT remains important. According to these authors, access to technology, the Internet, and ICT skills and attitudes are factors that are correlated with a more intense use of ICT among SMEs.…”
Section: Public Policy In Brazil ‐ Fostering Ict Access and Usagementioning
confidence: 99%
“…However, not all the population has the same level of digital literacy. Studies by Prodromou and Lavranos (2019) reveal lower levels of digital literacy in the elderly population, while Souza et al (2017) highlight the lower level of preparation of small and medium-sized enterprises to face the challenges of digitalization. In this sense, the initiatives that can be found in the EU countries to combat the effects of COVID-19 offer services, tutorials and applications for these two segments to be able to work with video conferencing systems and collaborative work, also ensuring mechanisms of privacy and security in access and exchange of information.…”
Section: Addressed Issuesmentioning
confidence: 99%